HRM PRACTICES AND EMPLOYEE RETENTION : THE MEDIATION EFFECT OF JOB SATISFACTION - Delfi Kurnia Zebua; Akmal Akmal; Zaitul Zaitul (Bajang Institute, 2022)
This study aims to test and prove the effect of compensation, training and development on lecturer retention with job satisfaction as the mediating variable. The population in this study were 275 people consisting of teaching staff throughout the District. Kerinci and the City of rivers are full. Where the sample in this study is 164 people with data that can be processed as many as 150 respondents, the type of data used is primary data. The data collection method is by distributing questionnaires. The analytical tool used in this study with the smart-PLS 3.2.7 software. The results showed that compensation had an effect on lecturer retention, as well as training and development had a significant effect on lecturer retention. However, job satisfaction has no effect on lecturer retention. On the other hand, compensation has an effect on job satisfaction, while training and development have no effect on job satisfaction. Furthermore, job satisfaction is not able to mediate the relationship of compensation, training and development to the retention of lecturers who are scattered in the Kab. Kerinci and the City of Sungai Penuh.